The changing environment of conservation conflict: Geese and farming in Scotland. Issue 2 (21st August 2017) - Mason, Tom H. E.; Keane, Aidan; Redpath, Stephen M.; Bunnefeld, Nils
Abstract: Conflict between conservation objectives and human livelihoods is ubiquitous and can be highly damaging, but the processes generating it are poorly understood. Ecological elements are central to conservation conflict, and changes in their dynamics — for instance due to anthropogenic environmental change — are likely to influence the emergence of serious human–wildlife impacts and, consequently, social conflict. We used mixed‐effects models to examine the drivers of historic spatio‐temporal dynamics in numbers of Greenland barnacle geese ( Branta leucopsis ) on the Scottish island of Islay to identify the ecological processes that have shaped the environment in which conflict between goose conservation and agriculture has been triggered. Barnacle goose numbers on Islay increased from 20, 000 to 43, 000 between 1987 and 2016. Over the same period, the area of improved grassland increased, the number of sheep decreased and the climate warmed. Goose population growth was strongly linked to the increasing area of improved grassland, which provided geese with more high quality forage. Changing climatic conditions, particularly warming temperatures on Islay and breeding grounds in Greenland, have also boosted goose numbers. As the goose population has grown, farms have supported geese more frequently and in larger numbers, with subsequent damaging effects on grassland. The creation of high‐quality grassland appears to have largely driven the problem of serious economic damage by geese. Our analysis also reveals the drivers of spatial variation in goose impacts: geese were more likely to occur on farms closer to roosts and those with more improved grassland. However, as geese numbers have increased they have spread to previously less favoured farms. Synthesis and applications . Our study demonstrates the primary role of habitat modification in the emergence of conflict between goose conservation and agriculture, alongside a secondary role of climate change. Our research illustrates the value of exploring socio‐ecological history to understand the processes leading to conservation conflict. In doing so, we identify those elements that are more controllable, such as local habitat management, and less controllable, such as climate change, but which both need to be taken into account when managing conservation conflict. Abstract : Our study demonstrates the primary role of habitat modification in the emergence of conflict between goose conservation and agriculture, alongside a secondary role of climate change. Our research illustrates the value of exploring socio‐ecological history to understand the processes leading to conservation conflict. In doing so, we identify those elements that are more controllable, such as local habitat management, and less controllable, such as climate change, but which both need to be taken into account when managing conservation conflict.